Maternal socio-economic and neonatal medical characteristics associated with survival of preterm neonates in Torit State Hospital, South Sudan: a descriptive cross-sectional study - Beatrice Doki; Pontius Bayo; Ronald Jada (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2023)
Introduction: One in 10 babies is born preterm globally. Preterm birth is a major cause of mortality among children under 5 years old especially in sub-Saharan Africa. The socio-economic and clinical characteristics associated with survival of preterm babies admitted in Torit State Hospital are unknown. This study describes these characteristics to inform quality-of-care initiatives to improve preterm neonatal care. Method: A retrospective study was conducted of the medical records of 67 preterm neonates admitted from 1st January to 31st December 2021. Neonatal outcome at discharge was recorded as alive, dead, or absconded while neonatal clinical and maternal socio-economic characteristics were recorded as independent variables. The data were analysed using SPSS Statistics software version 21. Descriptive statistics including frequencies and proportions were calculated. Differences in the proportions were tested using the chi-squared statistic. All significance levels were set at p ≤ 0.05. Results: Of the 67 preterm babies admitted, 47 (70.1%) were discharged alive with a significant increase in body weight, 18 (26.9%) died and the outcomes of two patients were not recorded. The ability to suckle at the time of admission (p=0.01) and having a mother educated to at least primary level (p=0.035) were significantly associated with higher preterm survival. Conclusions: Premature mortality was common among preterm babies who were not able to suckle at the time of admission and lack of formal maternal education was associated with low survival rates. Educating girls to at least primary level can contribute significantly to preterm neonatal survival.